Monotherapy and combination therapy with acitretin for mycosis fungoides: results of a retrospective, multicentre study. (22nd July 2020) - Nikolaou, V.; Patsatsi, A.; Sidiropoulou, P.; Chlouverakis, G.; Kavvalou, E.; Koletsa, T.; Economidi, A.; Georgiou, E.; Papadavid, E.; Rigopoulos, D.; Stratigos, A.J.; Kruger‐Krasagakis, S.E.
Abstract: Background: Retinoids have long been used in the treatment of cutaneous T‐cell lymphomas. However, data on acitretin use for mycosis fungoides (MF) are very limited. Objectives: To evaluate treatment outcomes of acitretin in patients with MF attending three academic referral centres in different regions of Greece. Methods: Data on effectiveness, safety and drug survival of acitretin as monotherapy or as adjuvant regimen were collected in a multicentre, register‐based, retrospective study. Results: Overall, 128 patients (64.8% male; mean age at MF diagnosis 59.7 years) were included. Folliculotropic MF was present in 24 (18.8%) cases. Most patients ( n = 118; 92.2%) had early‐stage disease (≤IIA) at acitretin initiation. In all, 28 (21.9%) patients received acitretin monotherapy, while 100 (78.1%) subjects on acitretin concomitantly received phototherapy ( n = 65; 50.8%) or topical steroids ( n = 27; 21.1%). Acitretin was given as a first‐line agent in 73 (57%) cases. A 77.3% overall response rate was noted: 44.5% and 32.8% for complete and partial responses, respectively. Acitretin was more effective as first‐line than as a subsequent agent ( P = 0.008). A trend towards better response was observed in the combination arm compared to patients receiving acitretin alone ( P = 0.056). Median time to best response was 6.9 months (IQR 4.4–9.4); median duration of response was 23.7 months (IQR 11.9–35.4). Overall, the mean length of all treatment patterns was 569 days (SD 718.8). Therapy was discontinued in 5 (3.9%) cases due to drug intolerance. Adverse effects were recorded in 62 (48.4%) cases with dyslipidaemia ( n = 31; 24.2%), xerosis ( n = 24; 18.6%) and hair loss ( n = 10; 7.8%) being the most commonly recorded. Conclusions: Acitretin, either alone or as adjuvant, showed a stable long‐term effectiveness in this cohort, especially when used in the first‐line setting. This RAR‐selective agonist may serve as an attractive option for treatment of MF and should be further evaluated.